APLICAÇÃO DE ANÁLISE ESTATÍSTICA NAS CURVAS σ-N DA LIGA DE ALUMÍNIO 7050-T7451 DE APLICAÇÃO ESTRUTURAL - Canto, Osmari Ademir Hoffmann do (2013)
Given the importance of presenting ever more reliable results with respect to the fatigue life of aluminum alloy 7050-T7451 application of this structural work guided their main focus on carrying out a statistical analysis of fatigue data collected from Axial fatigue tests conducted on specimens of this alloy. The data collected from these tests may be treated by various types of distribution functions, each function has some special features that have direct relation to the nature of the data collected thus different functions may have different results when applied to the same data set. Therefore it is not always clear which distribution function presented the results more reliable in relation to the data analyzed. For the statistical treatment of the data we used the statistical tool Minitab Release 13.0 which were analyzed four functions of distribution, Weibull, Lognormal Base and Loglogística and Normal. The choice of the function that best represented the data was based on two methods, graph method, where we obtained a qualitative analysis of the distribution of fatigue data and analytical method which produced a quantitative analysis of the results. For the definition of the function that showed the best results, comparisons were made of the most relevant statistics, especially the value of Anderson Darling test that was used in the work of adhesion. In addition to this statistical comparisons were also made errors regarding the probability of failure of 50% and also the values of the confidence intervals. The curves σ - N were plotted from the best figures for each voltage level. The results obtained after the statistical treatment of all values of fatigue life showed that for higher voltage levels (low cycle fatigue) any of the four functions studied can provide good adhesion to the fatigue data with errors quite small, as expected. For the values for medium voltage levels, which began to appear more substantial dispersions four functions still showed good adhesion, but showed most significant errors. When dealing with data sets of high cycle fatigue where stress levels were lower, the functions not performed well in fitting to the data, therefore, showed very high values of Anderson Darling statistic in which case the function is Loglogística was very efficient achieving produce good results even in groups where there were censored values (samples that did not fail). Thus it can be stated that the fatigue curves obtained from this method provide more reliable results, ensuring more security in predicting fatigue life of components built with aluminum alloy 7050-T7451.